2022
DOI: 10.1155/2022/9800993
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Severity of Disease and Postoperative Neurological Recovery in Patients with Cervical Spondylotic Myelopathy Combined with Developmental Spinal Stenosis

Abstract: Objective. The study aimed to investigate the correlation between the severity of disease and postoperative neurological recovery in patients with cervical spondylotic myelopathy (CSM) combined with developmental spinal stenosis. Methods. A retrospective analysis of the clinical data of 114 CSM patients combined with developmental spinal stenosis admitted to our hospital from June 2019 to June 2020 was performed. All of the patients who underwent posterior cervical unidoor vertebroplasty were divided into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%